МОДЕЛЬ ОПТИМАЛЬНОГО ВИКОРИСТАННЯ РЕСУРСІВ ГІДРОЕЛЕКТРОСТАНЦІЙ НА РИНКУ ЕЛЕКТРИЧНОЇ ЕНЕРГІЇ - Блінов, І.В.; Олефір, Д.О.; Парус, Є.В. (Інститут електродинаміки НАН України, Київ, 2022)
A mathematical model for optimizing the activity of the PJSC «Ukrhydroenergo» cascade of hydroelectric power plants in the segments of the electricity market is described. This model is built taking into account the limitations on the use of available water resources. The structure of the mathematical model as an objective function of maximizing the benefits of electricity sale and the system of restrictions of equality and inequality is presented. This function takes into account the economic and technical characteristics of power plant equipment, as well as the balance of hydro resources. Peculiarities of taking into account prices in electricity market segments are shown. The main technological constraints of hydraulic units and power plants are described. The structure of the system of restrictions on the use of water resources is reflected, taking into account changes in the levels of reservoir occupancy. The main approaches to the use of the proposed model to solve the problems of planning the participation of the cascade of hydropower plants in the auction of the electricity market are presented. References 16, figures 2.